Toxic effect of fear of losing out on self-esteem: A moderated mediation model of conformity and need for cognitive closure in Singapore - WEE, Sheila Xi Rui (Institutional Knowledge at Singapore Management University, 2022)
Kiasu (fear of losing out, FoLO) is considered the single most defining adjective that captures Singapore identity, and it is well-observed in other Asian cultures as well. Despite the widespread endorsement of kiasu in Singapore, there is limited empirical research on the theoretical conception of kiasu as a psychological construct. To empirically investigate kiasu, we validated the construct and measurement of the FoLO mindset in Study 1. In Study 2, we hypothesized and found a negative association between FoLO and Singaporeans’ self-esteem, which was mediated by a higher tendency of conformity. In addition, we hypothesized and found that individuals’ need for cognitive closure (NFCC) moderated the negative link between conformity and self-esteem such that high NFCC accelerated the negative impact of conformity on self-esteem. Whereas FoLO is often described as a form of competitiveness, the moderated-mediation model of FoLO and self-esteem can be replicated with competitiveness but in an opposite direction. This demonstrated that FoLO and competitiveness are two distinct psychological constructs. Implications of FoLO in Singapore as well as in other Asian contexts are discussed.